Nutritional consequences of breeding away from riparian habitats in Bank Swallows: new evidence from multiple endogenous markers. Issue 1 (19th January 2021) - Génier, Corrine S V; Guglielmo, Christopher G; Mitchell, Greg W; Falconer, Myles; Hobson, Keith A
Abstract : Bank Swallows ( Riparia riparia ) breed naturally in riparian habitats but also at inland human-made aggregate pits. Based on three endogenous markers used to track diet, we demonstrate that inland nesting results in nutritional consequences for young birds due to reduced provisioning of omega-3 fatty acids. Abstract: The Bank Swallow ( Riparia riparia ), a threatened species in Canada, breeds primarily in banks at lakeshores and rivers and in artificial (typically inland) aggregate mining pits. Inland pits may be ecological traps for this species, but relative dietary trade-offs between these two nesting habitats have not been investigated. The availability of aquatic emergent insects at lakeshores may have associated nutritional benefits for growing nestlings due to increased omega-3 fatty acids (FAs) in prey. We compared the diets of juvenile swallows from lakeshore and inland pit sites using assays of stable isotope values (δ 13 C, δ 15 N, δ 2 H) of feathers, faecal DNA metabarcoding and blood plasma FAs. Colony proximity to Lake Erie influenced the use of aquatic versus terrestrial insects by Bank Swallow adults and juveniles. Feather δ 2 H was particularly useful as a tracer of aquatic emergent versus terrestrial prey, and inland juveniles had feathers enriched in 2 H, reflective of diets composed of fewer aquatic emergent insects. DNA metabarcoding of juvenile and adult faecal material indicated that lakeshore birds consumed more aquatic-emergent chironomids than inland birds. Lakeshore juveniles had elevated plasma omega-3 eicosapentaenoic acid levels compared with inland pit-breeding birds. We discuss the need to consider 'nutritional landscapes' and the importance of this concept in conservation of declining species and populations.